THE SERIES OF GSM COMPUTER PROGRAMS FOR STATISTICAL MODELING IN THE GEOLOGICAL MONITORING TASKS - DEMYDOV, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The method and algorithm for statistical modeling of random processes and fields by software package GSM, using the methods of spectral decomposition and randomization, are considered. The algorithm, which is used in PPP GSM is tested for the monitoring of the location of lithotectonical foundation’s potentially dangerous objects.